Implementing JIGSAW Pedagogy to Enhance Learning in RES Course - Naik, Santosh Madeva; Mahajan, Hema; Sreeramulu, M.; Kannaiah, Ch. (Journal of Engineering Education Transformations, 2020)
The traditional way is no more effective way to enhance students learning and knowledge. However, students need different methods to learn the concept practically. Renewable energy is one subject from the mechanical stream where students are required active learning techniques to boost up their confidence towards the subject’s knowledge. Moreover, making students attentive during the class is a tough task and therefore implementing different pedagogy is needed to improve their understanding of the taught concept. This paper has explained the implementation of Jigsaw activity in the class and its impact on students learning.